THE EFFECTIVENESS OF TPRC STRATEGY FOR TEACHING READING COMPREHENSION OF DESCRIPTIVE TEXTS - S. Agustianingsih Nurul Anisah (INTERAKSI : Jurnal Kependidikan, 2018)
The purposes of the study were to find out the effectiveness of TPRC to teach reading comprehension and to find out whether there is any significant difference in students’ achievement of reading test between those who were taught using TPRC and those who were taught without using TPRC  This study applied a quasi-experimental design. The instrument used to collect data is test, that includes pre-test and post-test. The students in class X IPA , were chosen to be the participants of the study. class X IPA 2 was chosen to be the control group and class X IPA 1 was chosen to be the experimental group. The control group was taught by using conventional method (lecturing) given by teacher and the experimental group was taught by TPRC.  The result of the study indicated that the group taught by TPRC has better score in the test than the group taught by conventional method. The mean of posttest of experimental group (80.26) was higher than control groups (76.61). T-test calculation showed that there was a significant difference between post-test of control group and experimental group. TPRC strategy can be a helpful strategy for summarizing ideas from students about topic given. TPRC is effective for teaching reading comprehension of descriptive text and there was a significant difference in students’ achievement of reading test between those who taught using TPRC and those who taught without using TPRC.